Abundance of African invader fly, Bactrocera invadens drew, tsuruta and white (diptera: tephritidae) and influence of weather parameters on trap catches in mango in the Volta region of Ghana - Adzim, C.A.; Billah, M.K.; Afreh-Nuamah, K. (SpringerPlus, 2016)
The seasonal abundance of African Invader fly, Bactrocerainvadens and the influence of temperature and rainfall on fly catches was determined in two agro ecological zones; moist semi-deciduous forest area and the coastal grassland area of the Volta Region of Ghana for year of mango production. Traps containing methyl eugenol were used in monitoring the abundance of the Africa invader fly, Bactrocera invadens where data on both temperature and rainfall were collected from Meteorological Services of Ghana in Volta region. A total of 49,322 organisms captured, 45,829 were identified as Bactrocerainvadens and 3493 were non-fruit fly. There were significant differences (p < 0.05) in the number of Bactrocerainvadens captured between the agro ecological zones with relative fly densities of 5.06 F/T/D in moist semi deciduous forest area and 2.38 F/T/D in the coastal grassland zone. The result shows that climatic factors affected Bactrocerainvadens differently in different agro ecological area. There was negative correlation and highly significant (p < 0.001) correlation between fruit flies and temperature whereas there was negative correlation and high significant (p < 0.01) difference between rainfall in the moist semi deciduous forest area. In the coastal grassland area, there was negative correlation and highly significant (p < 0.001) between Bactrocerainvadens for both rainfall and temperature. Bactrocerainvadens activities peaked differently during the study period due to favourable climatic conditions. The activities of Bactrocerainvadens peaked during weeks 7 and 29 in the moist semi deciduous forest area while their activities peaked during weeks 3 and 24 for the coastal grassland areas. Both agro ecological zones recorded the presence of Bactrocerainvadens, their number and proportion varied considerably with associated effects of the weather parameters on their abundance. The effect of weather parameters on the abundance of bactrocera invadens requires the development of degree day models to manage them. © 2016, The Author(s).
Keywords: Agro ecological zones; Bactrocerainvadens; Correlation; Rainfall; Temperature